Variation of Bioactive Substances and Morphological Traits in Hypericum perforatum Populations from Northern Turkey - Çirak, C.; Radušiene, J.; (Saǧlam) Karabük, B.; Janulis, V. (Pergamon-Elsevier Science Ltd, 2007)
Hypericum perforatum L. has become one of the leading plant-based dietary supplements worldwide and its biological activities have been mainly attributed to hypericin and phenolic contents. The present study was conducted to determine chemical and morphological variability of H. perforatum sampled from different locations of Northern Turkey. The populations were investigated according to the hypericin, chlorogenic acid and the flavonoids, namely rutin, hyperoside, apigenin-7-O-glucoside, quercitrin and quercetin contents and morphological characters including leaf dark gland density, leaf area, leaf length/width ratio and plant height. Significant chemical and morphological variations were detected among the populations. Hypericin content among populations ranged between 0.44 and 2.82 mg/g dry weight, chlorogenic acid between 0.0 and 1.86 mg/g dry weight, rutin between 0.0 and 8.77 mg/g dry weight, hyperoside between 5.41 and 22.28 mg/g dry weight, quercitrin between 1.64 and 3.98 mg/g dry weight and quercetin between 1.01 and 1.76 mg/g dry weight. Hypericin content was found to be correlated positively with leaf dark gland density, however, negatively with leaf area and no correlation was detected between the other morphological traits and bioactive substances examined. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Apigenin-7-O-Glucoside; Chemical and Morphological Variability; Chlorogenic Acid; Hypericin; Hypericum Perforatum; Hyperoside; Quercetin; Quercitrin; Rutin; Wild Populations